2018
DOI: 10.1111/hsc.12565
|View full text |Cite
|
Sign up to set email alerts
|

Black/White disparities in pregnant women in the United States: An examination of risk factors associated with Black/White racial identity

Abstract: This paper explores racial disparities and risk factors of adverse pregnancy outcomes in Black and White pregnant women in the US. The study uses a cross-sectional approach to explore Black and White disparities using data from the 2012 National Survey on Drug Use and Health (NSDUH), which collects interview data from approximately 70,000 randomly selected participants. We included several self-reported conditions that we categorised as individual and social stressors (e.g. measures of institutionalised racism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…In contrast to a study which indicated that NH Black women had lower employment levels 10 , in the present research, a higher percentage of NH White women stated that they were not expecting to work next year (e.g. had a lower percentage of employment levels).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to a study which indicated that NH Black women had lower employment levels 10 , in the present research, a higher percentage of NH White women stated that they were not expecting to work next year (e.g. had a lower percentage of employment levels).…”
Section: Discussioncontrasting
confidence: 99%
“…There were categories for missing and excluded data, assessed by such categories as refused, do not know, missing, multiple answers, not asked, skipped, or n/a (which were not used in this study). Similar to other studies only assessing Black/White disparities 10 , 11 , the populations of interest in this study were only NH Blacks and Whites.…”
Section: Methodsmentioning
confidence: 98%
“…Institutionalized racism is a fundamental cause of the limited resources in Black communities as it results in lower income, inequality in social environments, and less access to health insurance and gainful employment opportunities. 18,[42][43][44] This dearth of resources is a deterrent to attracting highly skilled healthcare providers and community resource investment. Furthermore, this lack of resources and standardized practices may be detrimental during times of health care crises.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…The field of maternal and child health offers a compelling example of well-documented evidence demonstrating the role that racism plays on health outcomes [36,37]. Specifically, public health scholarship has exhaustively documented the elevated risk of maternal and infant complications during pregnancy for Black women (when compared to White women) [38][39][40].…”
Section: Introductionmentioning
confidence: 99%